Indoor air report breathe easy (Virginia : Coastal Video Communications, 1994)
Disscused on clean air and indoor air quality
Video is accompanied by 10 handbooks of Indoor air quality
Copy available in DVD format
Keywords: Indoor air pollution; Air quality